The Rise and Fall of American Humor - Bier Jesse (Holt, Rinehart And Winston, 1968)
Preface, Introduction, Early American Humor, ''Southwestern'' Humor, ''Literary Comedians'': The Civil War and Reconstruction, Mark Twain, Intercentury Humor, Interwar Humor, Modern American Humor, Humor in Selected Major American Writers, American and Foreign Humor, Conclusion, Bibliography, Index.
Preface, Introduction, Early American Humor, ''Southwestern'' Humor, ''Literary Comedians'': The Civil War and Reconstruction, Mark Twain, Intercentury Humor, Interwar Humor, Modern American Humor, Humor in Selected Major American Writers, American and Foreign Humor, Conclusion, Bibliography, Index.